3D porous graphitic nanocarbon for enhancing the performance and durability of Pt catalysts: a balance between graphitization and hierarchical porosity. Issue 9 (31st July 2019) - Qiao, Zhi; Hwang, Sooyeon; Li, Xing; Wang, Chenyu; Samarakoon, Widitha; Karakalos, Stavros; Li, Dongguo; Chen, Mengjie; He, Yanghua; Wang, Maoyu; Liu, Zhenyu; Wang, Guofeng; et al.
Abstract : A carbon support with favorable balance between graphitization and hierarchical porosity is promising to address carbon corrosion issue in cathode catalysts for proton exchange membrane fuel cells (PEMFCs). Abstract : Carbon supports used in oxygen-reduction cathode catalysts for proton exchange membrane fuel cells (PEMFCs) are vulnerable to corrosion under harsh operating conditions, leading to poor performance durability. To address this issue, we have developed highly stable porous graphitic carbon (PGC) produced through pyrolysis of a 3D polymer hydrogel in combination with Mn. The resulting PGC features multilayer carbon sheets assembled in porous and flower-like morphologies. In situ high-temperature electron microscopy was employed to dynamically monitor the carbonization process up to 1100 °C, suggesting that the 3D polymer hydrogel provides high porosity at multiple scales, and that Mn catalyzes the graphitization process more effectively than other metals. Compared to conventional carbon supports such as Vulcan, Ketjenblack, and graphitized carbon, PGC provides an improved balance between high graphitization and hierarchical porosity, which is favorable for uniform Pt nanoparticle dispersion and enhanced corrosion resistance. As a result, Pt supported on PGC exhibits remarkably enhanced stability. In addition to thorough testing in aqueous electrolytes, we also conducted fuel cell testing using durability protocols recommended by the U.S. Department of Energy (DOE). After 5000 voltage cycles from 1.0 to 1.5 V, the Pt/PGC catalyst only lost 9 mV at a current density of 1.5 A cm −2, dramatically exceeding the DOE support durability target (<30 mV), and surpassing commercial Pt/C catalysts. Along with the enhanced carbon corrosion resistance of the PGC support, the enhanced catalyst–support interactions are beneficial for stability improvement, likely due to nitrogen doping into carbon, which was further elucidated through X-ray absorption spectroscopy and density functional theory (DFT) calculations. Thus, the high stability and activity of PGC-based Pt catalysts are attributed to the combination of high graphitization degree, favorable surface area and porosity, and nitrogen doping, which effectively stabilize highly dispersed Pt nanoparticles.